2018
DOI: 10.1016/j.virol.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

MARCH2 is upregulated in HIV-1 infection and inhibits HIV-1 production through envelope protein translocation or degradation

Abstract: MARCH2 is one of the MARCH family E3 ligases, which contains eleven members that play pivotal roles in controlling the turn-over of membrane proteins, such as MHC class I, MHC class II, and cell surface receptors. In this study, we found the expression of MARCH2 to be upregulated upon HIV-1 infection. MARCH2 inhibits the production and infection of HIV-1 through ligase activity-dependent envelope protein degradation and/or intracellular retention, a mechanism shared by MARCH8 that also leads to the inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 31 publications
1
40
3
Order By: Relevance
“…Zhang et al (30) recently reported that MARCH2 is up-regulated by HIV-1 infection and reduces viral production without being incorporated into virus particles. We were, however, unable to observe the same phenomenon (Fig.…”
Section: March1 and March2 Inhibit Hiv-1 Infectionmentioning
confidence: 99%
“…Zhang et al (30) recently reported that MARCH2 is up-regulated by HIV-1 infection and reduces viral production without being incorporated into virus particles. We were, however, unable to observe the same phenomenon (Fig.…”
Section: March1 and March2 Inhibit Hiv-1 Infectionmentioning
confidence: 99%
“…In the context of exogenous retrovirus infections, more than nine groups of cellular restriction factors have been reported to interfere with Human Immunodeficiency Virus type 1 (HIV-1) replication. They include the well-characterized APOBEC3G, SAMHD1, Tetherin/BST-2, and TRIM5α proteins (Johnson, 2013), and those more recently characterized such as MX-2, SERINC3/5, IFITMs, Schlafen 11, and MARCH2/8 (Goujon et al, 2013;Zhang et al, 2018). Relevant to this, endogenized HERVs can be potentially considered per se as restriction factors able to exert protective effects against exogenous retroviruses (Grandi and Tramontano, 2018a).…”
Section: Herv and Antiviral Activitymentioning
confidence: 99%
“…These factors drive Env down-regulation from the plasma membrane and its intracellular sequestration to decrease Env incorporation into newly produced HIV-1 virions (15). In addition, MARCH2 was found to be upregulated upon HIV-1 infection in Jurkat and THP-1 cells promoting Env ubiquitination and its subsequent lysosomal degradation (16). These observations suggest a possible activity for MARCH2 in redirecting Env glycoproteins via the lysosomal route to antigen presentation pathways.…”
Section: Restriction Factors: Intrinsic Antiviral Activity and Modulamentioning
confidence: 99%
“…They are generally interferon (IFN)-inducible and their inherent features, such as constitutive expression in different cell types, self-sufficient activity, and rapidity of action, confer a potent and early restriction of viruses (1). So far, more than nine groups of cellular restriction factors have been identified that inhibit Human Immunodeficiency Virus type 1 (HIV-1), and other primate lentiviruses, including the classical and well-documented APOBEC3G, SAMHD1, Tetherin/BST-2, and TRIM5α (210), and those of more recent characterization MX-2, SERINC3/5, IFITMs, Schlafen 11, and MARCH2/8 (1116). The continuous adaptation of HIV-1 to the pressure exerted by the antiviral activities of restriction factors underscores the importance of restriction factors in controlling viral infections.…”
Section: Introductionmentioning
confidence: 99%